Aktivitas Anti-Inflamasi Bawang Hitam (Allium sativum L.) - Qotrunnada Salsabila; Hendri Busman (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: Inflammation is a series of non-specific innate processes that are activated by the body in response to foreign invasion, tissue damage, or both. Purpose: To determine the anti-inflammatory activity of black onions. Methods: using literature studies from national and international journals by summarizing discussion topics and comparing the results in articles. Results: Black onions have anti-inflammatory activity through their bioactive components S-allyl cysteine, polyphenols, and flavonoids and can be used as an alternative anti-inflammatory agent in phytopharmaca. Conclusion; The fermentation process carried out by heat treatment at certain humidity in garlic will produce an end product in the form of black garlic or aged black garlic